Coordination and order risk assessment of water and land resource system based on periphery and synergetics theories - Jiang, Qiuxiang; Zhou, Zhimei; Wang, Zilong; Fu, Qiang; Zhao, Youzhu; Wang, Tian (International Journal of Agricultural and Biological Engineering, 2018)
Coordinated and orderly water and land resource system is vital to ensure the economic and social development of a region. Grain production in Heilongjiang Province has increased consecutively every year since 2003, and numerous water and land resource-related problems have become increasingly prominent and have had significant adverse effects on social and economic development and stability in the region. In this study, Heilongjiang Province and its 13 prefecture-level cities were selected as the study area, and the degrees of coordination of the social, economic and ecological subsystems were evaluated using periphery theory and the theory of synergetics. To ensure that the assessment was objective and accurate, weights were calculated using the projection pursuit technique, and similarity degrees were calculated using a modified (by introducing the chi-square distance) order of preference by similarity to ideal solution (TOPSIS) technique. Moreover, to reflect the variations in the overall degree of coordination in Heilongjiang Province, the risk level of the coordination of the water and land resource system was predicted through the year 2020 using a dynamic neural network. This study provides a reference for establishing effective and balanced coordination between society and water and land resources.Keywords: water and land resources, periphery theory, coordination, particle swarm optimization, neural networkDOI: 10.25165/j.ijabe.20181103.3508Citation: Jiang Q X, Zhou Z M, Wang Z L, Fu Q, Zhao Y Z, Wang T. Coordination and order risk assessment of water and land resource system based on periphery and synergetics theories. Int J Agric & Biol Eng, 2018; 11(3): 146–153.